Ontologically Sound Basis for Analyzing Academia, Digitalization and Entrepreneurship Together: A Solution to the Sociomaterialistic Puzzle of "Strong Relationality" - Poutanen Seppo (Routledge, 2022)
How should research on academia and digitalization, in relation to entrepreneurship, be undertaken? This question is both banal and intriguing. If one does indeed need models for such a study, one can be referred to rapidly growing research libraries, collections of journal articles, etc., in which these three concepts are theorized and defined in numerous ways, as well as variously combined for the needs of versatile analyses of related empirical phenomena.
Digital Work and the Platform Economy